Global strategy: An organizing framework - Ghoshal, Sumantra (Strategic Management Journal, 1987)
Abstract Global strategy has recently emerged as a popular concept among managers of multinational corporations as well as among researchers and students in the field of international management. This paper presents a conceptual framework encompassing a range of different issues relevant to global strategies. The framework provides a basis for organizing existing literature on the topic and for creating a map of the field. Such a map can be useful for teaching and also for guiding future research in this area. The article, however, is primarily directed at managers of multinational corporations, and is aimed at providing them with a basis for relating and synthesizing the different perspectives and prescriptions that are currently available for global strategic management.